Analisis Strategi Pemasaran Kedai Usaha Mie Jeng-Kang Menurut Perspektif Etika Bisnis Islam - Hasilatun Rizqo; Tati Handayani (Islamic Economics and Business Review, 2022)
The business world has developed rather quickly, one of the issues that frequently arises has to do with marketing. Creating a suitable plan is essential to achieving business goals. Every company has a unique marketing plan, however there are many businesspeople who continue to be challenging and frequently fail to grow their companies. The purpose of this study is to find out how to apply the marketing strategy of Kedai Usaha Mie Jeng-Kang according to the perspective of Islamic business ethics. This research was conducted with a descriptive qualitative approach and is a field research. From the study's findings, it can be inferred that Kedai Usaha Mie Jeng-Kang uses a 4P marketing mix, which includes a product strategy for cuisine manufactured from instant noodles, a pricing point that is affordable, a location that is spacious, cool and suitable facilities. Adequate offline promotion is done via word of mouth and personal contact, while online promotion is done via social media. Based on the perspective of Islamic business ethics, the marketing carried out is in accordance with Islamic marketing ethics which consists of the ethics of piety, shidiq, al-adl, khidmah, al-amanah, keeping promises, husnudzon, not doing backbiting and not doing riswah.